Relationships between Body Morphometries and Testicular Biometrics of West Africa Dwarf Bucks in Southwestern Nigeria (2014)
In a study to determine the relationships between body morphometrics and testicular biometrics, 30 healthy West Africa Dwarf bucks belonging to three age groups, 0.5 to 1.0 years (group A), = 1.5 to 2.0 years (group B) and 2.5 to 3.0 years (group C) were evaluated. The animals were tagged and body measurements were recorded before the animals were sacrificed. The external and internal parameters of the testis were measured and recorded accordingly. The mean values for body weight were 6.92±0.06Kg, 8.93±0.69Kg and 11.67±0.33Kg for age groups A, B and C respectively. Animals in age group C recorded the highest mean value for heart girth, body weight, paunch girth and wither height. A predictive model for each of the testicular characteristics was developed using live body measurement. Age was significantly (P<0.05) positively correlated with all body and testicular measurement, but not with testicular density and caput weight. However, scrotal circumference was significantly (P<0.001) correlated with testicular length (r = 0.557), testicular diameter (r = 0.595), testicular weight (r = 0.617) and caudal weight (r = 0.663), while the correlation with testicular density was significant at P<0.01. Body weight was positively correlated (P<0.01) with scrotal circumference (r = 0.455), testicular length (r = 0.694), testicular diameter (r = 0.618), testicular volume (r = 0.668), testicular weight (r = 0725), corpus weight (r = 0.705) and caudal weight (r = 0.687). Based on the findings in this study, it is concluded that bucks can be selected for breeding purposes on the bases of measurements of scrotal circumference, testicular length and testicular diameter